Optimization of cutting forces and surface roughness via ANOVA and grey relational analysis in machining of In718 - AY, MUSTAFA (My University, 2023)
Machinability and optimization are the two objectives of researchers who guide us to enhance the manufacturing industry. Examining and analyzing the parameters such as surface roughness, tool wear, and cutting force during the processing would be beneficial that are used in various fields in the manufacturing industires. This study examined the effect of cutting forces to surface roughness on the material surface. Experimental studies were carried out by using constant feed rate (0.1 mm/rev), depth of cut (1 mm), three different coolants (CO2, minimum quantity lubrication, and dry), and cutting speeds (100, 140, 180, 220 m/min). In this study, grey relational analysis modeling and analysis of relationships betweenFx,Fy, andFzforces on the surface roughness of Inconel 718 material, which is an important alloy in aviation, is examined. The influence of machinability parameters onFtopandRawas calculated using variance analysis, which determined that cutting speed was the most significant machining parameters.
Keywords: Diğer; Makina Mühendisliği; Konstrüksiyon ve İmalat; Talaşlı İmalat Yöntemleri; Mühendislik ve Teknoloji; Other; Mechanical Engineering; Construction and Manufacturing; Machining Methods; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Fizik Bilimleri; Computational Mechanics; Automotive Engineering; Physical Sciences; surface roughness; Inconel 718; machinability; Taguchi; optimization; grey relation; ANOVA